Management in Monetary Authority (Case of Jordan) (Global Journal of Management and Business Research, 2019)
This research aims at demonstrating how to manage the relationship between central banks and Islamic banks, a sample has been taken and the Central Bank of Jordan and Islamic banks operating in Jordan, through addressing the tools of the Central Bank of Jordan control of Islamic banks operating in Jordan and the use of a comparative approach between Islamic banks and conventional banks and the fundamental differences between them to clarify more some things in general and the legislation governing the work Islamic banks in Jordan, and finally the most important problems facing Islamic banks with central banks. In this research, we have concluded that Islamic banks are supervised and controlled in the framework of the unified approach, despite this, it is achieving remarkable success and it will continue to progress and consolidate its steps despite the difficulties and internal and external obstacles, the research was concluded with a number of recommendations for Islamic banks to invest their money in more investments and expand in other Shariah formulas and qualify employees and develop their skills, and recommendations of the Central Bank of Jordan may contribute to the Central Bank of Jordan to amend some of the control tools and the introduction of new elements in favor of Islamic banks and the creation of new investments in line with them, which may lead to the investment of Islamic banks excess liquidity, which is reflected in increasing profitability and increase the proportion of returns distributed On the accounts of its customers and work to separate the data and information in the reports and bulletins related to Islamic banks.
Keywords: management; monetary; authority; Jordan